PENGEMBANGAN INTELLIGENT MOBILE LEARNING BERBASIS KODULAR PADA MATERI BILANGAN BULAT UNTUK MEMFASILITASI PEMAHAMAN KONSEPTUAL MATEMATIS - Emmy Lufian; Riskayani Jaida; Zulfadli Takdir; Sri Sulasteri; Ahmad Farham Majid (Jurnal Ilmiah Matematika Realistik, 2026)
Mathematical conceptual understanding is one of the essential competencies that students must possess to face the challenges of 21st-century learning. However, students’ understanding of mathematical concepts, particularly in integer material, is still relatively low. In addition, Android-based learning media that have been developed generally focus only on delivering materials and simple exercises, so they have not been able to facilitate conceptual understanding in an interactive and contextual manner. Therefore, this study aims to develop Kodular-based Intelligent Mobile Learning on integer material to facilitate students’ mathematical conceptual understanding. This study employed a Research and Development (R&D) method using the ADDIE development model, which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. The study involved 35 seventh-grade students of MTs Madani Alauddin, Gowa Regency. The developed product was an Android-based learning application equipped with interactive materials, learning videos, example problems, practice exercises, quizzes, discussions, and automatic feedback features. The validation results indicated that the developed media was highly valid, with material expert validation reaching 89.25% and media expert validation reaching 91.11%. The implementation of the media also showed positive results, with student responses reaching 85.14% and teacher responses reaching 89.27%, both categorized as very good. In addition, the implementation results demonstrated high effectiveness with an N-Gain score of 0.72. The findings indicate that the Kodular-based Intelligent Mobile Learning is valid, practical, and effective in facilitating students’ mathematical conceptual understanding of integer material. Thus, the development of Kodular-based learning media can serve as an innovative solution to support interactive mathematics